2016
DOI: 10.1038/nbt.3471
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic genome editing by combined viral and non-viral delivery of CRISPR system components in vivo

Abstract: The combination of Cas9, guide RNA and repair template DNA can induce precise gene editing and the correction of genetic diseases in adult mammals. However, clinical implementation of this technology requires safe and effective delivery of all of these components into the nuclei of the target tissue. Here, we combine lipid nanoparticle–mediated delivery of Cas9 mRNA with adeno-associated viruses encoding a sgRNA and a repair template to induce repair of a disease gene in adult animals. We applied our delivery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
633
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 774 publications
(647 citation statements)
references
References 47 publications
6
633
1
7
Order By: Relevance
“…[[qv: 5b,6]] However, the possible cytotoxicity, immunogenic response, long‐term expression, and off‐target effects of viral vectors, continue to be the clinical application concern 7. Also, the nonviral delivery methods, such as electroporation,[[qv: 7a]] microinjection,8 lipid and lipid‐like nanoparticles delivery,9 and ribonucleoprotein delivery10 are reported, which are also limited by their stability, accessibility, safety, or efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[[qv: 5b,6]] However, the possible cytotoxicity, immunogenic response, long‐term expression, and off‐target effects of viral vectors, continue to be the clinical application concern 7. Also, the nonviral delivery methods, such as electroporation,[[qv: 7a]] microinjection,8 lipid and lipid‐like nanoparticles delivery,9 and ribonucleoprotein delivery10 are reported, which are also limited by their stability, accessibility, safety, or efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Cas9-based genome editing agents can mediate targeted gene disruption or repair 1013 . For applications that seek a one-time, permanent modification of genomic DNA, we and others have shown that the delivery of non-replicable, transient Cas9:single guide RNA (sgRNA) ribonucleotide protein (RNPs) complexes in vivo offer improved DNA specificity and potentially greater safety and applicability 14,15 compared with methods that introduce DNA expressing these agents.…”
mentioning
confidence: 99%
“…In conclusion, these recent advances [10][11][12]14,15 represent significant steps forward to the final application of CRISPR-Cas9 to human gene therapy. However, there are still many challenges lying ahead, such as delivery efficiency, HDR efficiency, off-target effects and the fitness of edited cells.…”
mentioning
confidence: 98%
“…In these two studies, the authors used either a dual viral vector systems 14 or a combination of viral vector and lipid nanoparticles 15 to deliver the three therapeutic components of CRISPR-Cas9 (sgRNA, Cas9 and donor template), and gained a HDR efficiency level sufficient to rescue the disease phenotypes in mouse models of human hereditary liver diseases whose treatments necessitate HDR-mediated gene replacement.…”
mentioning
confidence: 99%
See 1 more Smart Citation